Retinal nerve fibre layer thickness changes in Alzheimer's disease: Results from a 12-month prospective case series. (26th August 2016) - Trebbastoni, Alessandro; D'Antonio, Fabrizia; Bruscolini, Alice; Marcelli, Michela; Cecere, Michela; Campanelli, Alessandra; Imbriano, Letizia; de Lena, Carlo; Gharbiya, Magda
Highlights: Progressive thinning of the retinal nerve fibre layer by SD-OCT in AD has been described in this prospective comparative case series on AD patients. The progression of the retinal abnormalities found AD participants correlated with their cognitive decline over time. Repeated measurements of the retinal nerve fibre layer could serve as a new potential dynamic AD biomarker in the eye. Abstract: Purpose: To compare the 12-month peripapillary retinal nerve fibre layer (pRNFL) thickness change between AD patients and normal subjects. Methods: In this prospective case series, thirty-six patients with a diagnosis of mild to moderate AD and 36 age-matched control subjects were included. All the subjects underwent neuropsychological (MMSE, ADAS-Cog and CDR) and ophthalmological evaluation, including spectral domain optical coherence tomography (SD-OCT), at baseline and after 12 months. Results: Compared with controls, AD patients had a significant reduction of the total pRNFL thickness, as well as the pRNFL thickness of the inferior and superior quadrants (p = 0.04, p = 0.001, and p = 0.01, respectively, adjusted for baseline pRNFL measurement, age, gender, and axial length). Correlation analysis showed a significant relationship between inferior pRNFL thickness change and ADAS-Cog scores change (r = −0.35, p = 0.02) as well as CDR scores at 12 months (r = −0.39, p = 0.008). Conclusions: Compared with controls, AD patients had a significant reduction in pRNFL thickness over a period of 12 months. The pRNFL reduction was more prominent in the inferior quadrant and paralleled patient's cognitive decline.